Knowledge and practice on infection control amongst students of the International Islamic University Malaysia (IIUM) during clinical attachment - Rosli, Nur Afifah; Moey, Soo Foon; Che Mohamed, Norfariha (IIUM Press, 2022)
Introduction: Hospital acquired infection (HAIs) has been indicated as the major barrier to patient care as it is contributory to the increase in morbidity, mortality and financial strain. In clinical department such as the Medical Imaging department, there is a high interaction between the patients, staff and even students who are doing their clinical attachment. As such, students can possibly spread HAI through poor knowledge and practices which can then affect the healthcare quality. Objective/aim: This study aims in ascertaining the knowledge and practice level of Infection Control Precaution (ICP) amongst the undergraduate Medical Imaging students at International Islamic University Malaysia (IIUM). Materials and methods: A survey was carried out on 63 Year Two to Year Four students that were selected randomly. The data was analysed using descriptive analysis and Kruskal Wallis test. Results: Poor knowledge and practices of ICP were indicated amongst the respondents. The Kruskal Wallis test indicated no significant difference of ICP practices between the second, third and fourth-year students. The overall knowledge and practice scores of ICP amongst respondents were found to be poor despite it having been taught in the Patient Care course. This could probably be due to the method of delivery of the subject matter, workload, forgetfulness and myth of skin allergy that can be combatted with education. Conclusion: The insignificance between the practice of ICP and the year of study of the respondents can be addressed by providing the necessary training, monitoring on ICP including the evaluation of ICP to improve the effectiveness of adherence to ICP.